A Survey of Bronchoscopy Practice in Australia and New Zealand. Issue 1 (January 2016) - Barnett, Adrian M.; Jones, Rhondda; Simpson, Graham
Abstract : Background: The authors assessed the variability of bronchoscopy practice in Australia and New Zealand through survey in the setting of recently published guidelines. Methods: In June 2014, an email survey was sent to every member of The Thoracic Society of Australia and New Zealand who was a doctor. Results: Responses were received from 258 of 824 doctors. Australia and New Zealand was the location of training for 91% and the United Kingdom for 9%. United Kingdom–trained doctors are more likely to conduct bronchoscopy from the patient's side rather than from behind. The services of anesthetists are utilized by 81% of private bronchoscopists compared with 38% of public ones. Two sedatives are used by 94% of bronchoscopists, 96% of whom use midazolam and fentanyl and 4% use midazolam and propofol. When anesthesia is provided by anesthetists, 77% use 2 agents, of which 53% use midazolam and fentanyl and 37% use midazolam and propofol. Those who work publicly conduct more procedures and are younger. For patients with heart valve defects, 39% prescribe prophylactic antibiotics and 16% do not cease clopidogrel where biopsy is anticipated. In 2013, pneumothoraces complicated 0.22% of procedures, whereas the mortality rate was 0.019%. Almost all monitor oxygen saturation during the procedures. Conclusions: This survey shows that there is a large variation in bronchoscopy practices both generally and between different groups of bronchoscopists, yet it is a safe procedure. An important finding was the significantly high utilization of the services of anesthetists for sedation and their different sedative choices, including the use of propofol.